2015
DOI: 10.1007/s13277-015-4086-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a regulates the proliferation, migration, and invasion of human osteosarcoma by targeting Runx2

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor in young patients. However, treatment paradigms and survival rates have not improved in decades. MicroRNAs have been shown to be critical regulators of physiological homeostasis and pathological process, including bone disease. Nearly half of the microRNA (miRNA) genes are located at genomic regions and fragile sites known to be frequently deleted or amplified in various kinds of cancers. In this study, we investigated the role miR-30a in OS. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Several studies have reported the significance of miRs in relation to OS including miR-101, miR-26b and miR-30a [1618]. In the present study, it was established that miR-379 exhibited a low level of expression in U2OS and MG-63 cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies have reported the significance of miRs in relation to OS including miR-101, miR-26b and miR-30a [1618]. In the present study, it was established that miR-379 exhibited a low level of expression in U2OS and MG-63 cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, RUNX2 can promote the metastasis of human gastric cancer through up-regulation of the chemokine receptor CXCR4 [16]. Furthermore, the critical role of miR-30a in inhibiting the progression of human osteosarcoma is mediated by targeting RUNX2 [17]. RUNX2 is also confirmed as a target of miR-338-3p to mediate the tumor-suppressive function of miR-338-3p in ovarian epithelial carcinoma [18].…”
Section: Introductionmentioning
confidence: 97%
“…In most studies, these miR-30 family members have been shown to function as tumor suppressors that act to constrain the development of various cancers [7][8][9][10][11][12][13][14][15]. Among the miR-30 members, miR-30a had drawn much attention due to its functions in inhibiting primary tumor growth or metastasis formation in several cancer types, especially in breast cancer [8][9][10][11][12]. When miR-30a expression was decreased in breast tumors, this was linked with higher rates of lymph node metastasis, p53 inactivation, and poorer patient prognosis [6].…”
Section: Introductionmentioning
confidence: 99%